Die Anwendung radiochemischer Analysenmethoden zur Bestimmung von Zink- und Calciumspuren in Gallium - Pierre Lerch; Leo Kreienbühl (CHIMIA)
The method ot thermal neutron activation analysis has been utilized for the determination of calcium and zinc traces in metallic gallium. This method allows to measure amounts of calcium as low as one p.p.m. by counting the calcium-45β-activtity after chemical separation. In return, the method could not be used for zinc traces, as a  (n,p) nuclear reaction appeared in presence of the fast neutrons.